2019
DOI: 10.1039/c8ob01947a
|View full text |Cite
|
Sign up to set email alerts
|

A dual modality99mTc/Re(i)-labelled T140 analogue for imaging of CXCR4 expression

Abstract: A T140-derived peptide conjugated with a naphthalimide fluorophore/chelator was coordinated to rhenium or technetium-99m to image CXCR4 expression by fluorescence microscopy or SPECT imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…During the course of these studies, Luyt and co-workers reported a peptide-functionalised naphthalimide-based fluorophore that can be used to target CXCR4 expressing cells for potential dual mode imaging. 40 This further suggests that the inherent fluorophore-chelate design presented herein holds great promise for future biological and bioimaging applications.…”
Section: Discussionmentioning
confidence: 83%
“…During the course of these studies, Luyt and co-workers reported a peptide-functionalised naphthalimide-based fluorophore that can be used to target CXCR4 expressing cells for potential dual mode imaging. 40 This further suggests that the inherent fluorophore-chelate design presented herein holds great promise for future biological and bioimaging applications.…”
Section: Discussionmentioning
confidence: 83%
“…For example, C–X–C chemokine receptor 4 (CXCR4) is overexpressed in over 23 different types of cancer and is more prevalent in malignant cancer tissue [ 176 ]. With this consideration, a rhenium(I) tricarbonyl complex was conjugated to a derivative of T140 (14 amino acid sequence), a known antagonist of CXCR4, and showed potential as an imaging agent for CXCR4 expression that was capable of differentiation between cancerous and healthy tissue [ 177 , 178 ]. Kuil and co-workers had previously presented an iridium(III)–peptide conjugate for FLIM-based visualisation of CXCR4 expression in cells by conjugating the complex to a series of Ac-TZ14011 peptides [ 179 ].…”
Section: Rationale For Peptide Conjugation To Transition Row Metal Co...mentioning
confidence: 99%
“…As mentioned earlier, a rhenium(I) tricarbonyl complex was conjugated to a derivative of T140 , a known antagonist of CXCR4 and a chemokine receptor which is overexpressed in cancer cells [ 177 ]. The rhenium conjugate was successful in sensing CXCR4, evident by a strong luminescence signal detected from cells expressing CXCR4, whereas no luminescence was detected from cells lacking the receptor.…”
Section: Sensing Capabilities Of Peptide Metal Complex Conjugatesmentioning
confidence: 99%
“…Due to inevitably high non-specific background accumulation in the excretion organs, in particular in the liver, T140-based ligands such as [ 68 Ga]NOTA-NFB imaging deliver up to ten times higher effective doses in patients compared to [ 68 Ga]Pentixafor [ 95 , 96 ], challenging their potential for further clinical application. Thus, not surprisingly, only one novel T140—based compound (for SPECT imaging) has been published since 2019 (entry 21, Table 1 ), displaying the same characteristics as previous probes based on this scaffold [ 85 ].…”
Section: Cxcr4-targeted Imaging Agents: An Ever-evolving Fieldmentioning
confidence: 99%